Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Terumbu Karang Melalui Proses Presipitasi Dengan Variasi Rasio Ca/P Dan PH - Mahdi, Zamratul; Azis, Yelmida; Fadli, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Hydroxyapatite is a crystalline molecule composed of phosphorus and calcium with the molecular formula Ca10 (PO4) 6 (OH) 2. Synthetic hydroxyapatite is known as one of the important implant materials because it has bioactive, biocompatible and osteoconductive properties that chemically resemble the mineral components of bones and teeth, so that it can be used as a substitute for human hard tissue. In this study hydroxyapatite synthesized from PCC coral reef using precipitation method with variations in pH (9, and 11) and Ca / P mole ratio (1.60; 1.67; 1.70; 1.77 and 1.80). The hydroxyapatite obtained was then analyzed by XRD and SEM analysis. From the results of XRD and SEM analysis obtained the best hydroxyapatite with the best crystallinity closest to standard hydroxyapatite, pH 11 Ca / P 1.60 ratio with 88.7% crystallinity and 26.9 nm crystal size Keyword: carbonation, Ca / P ratio, PCC, pH, precipitation,